Peran Bawaslu Kota Surabaya dalam Mencegah Pelanggaran Pilkada Serentak 2024 - Risaldi, Muhammad; Arif, Lukman (VISA: Journal of Vision and Ideas, 2025)
The aim of this scientific paper is to examine the role of the Surabaya City General Election Supervisory Agency (BAWASLU) regarding preventing violations of the 2024 Simultaneous PILKADA. This scientific paper utilizes a qualitative, descriptive approach by focusing on data sources originating from educational content analysis on social media, observation of innovation. BAWASLU program with direct observation and also supported by the regulations of Law No. 7 of 2017 concerning ELECTIONS, books and journals that are relevant to written work This is scientific. In this scientific paper, it is found that the role of BAWASLU is very vital in ensuring a clean, honest and fair Regional Head Election Process, with socialization and various innovations with the aim of building community sensitivity to the importance of Citizen participation in preventing violations of the PILKADA, understanding the rights and obligations of the community in PILKADA and BAWASLU carry out collaboration and coordination between the general public and related agencies, institutions and parties with the aim of maximizing prevention of violations in the 2024 Simultaneous PILKADA.